2022
DOI: 10.3390/cells11142225
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional Regulation of the Hippo Pathway: Current Understanding and Insights from Single-Cell Technologies

Abstract: The Hippo pathway regulates tissue homeostasis in normal development and drives oncogenic processes. In this review, we extensively discuss how YAP/TAZ/TEAD cooperate with other master transcription factors and epigenetic cofactors to orchestrate a broad spectrum of transcriptional responses. Even though these responses are often context- and lineage-specific, we do not have a good understanding of how such precise and specific transcriptional control is achieved—whether they are driven by differences in TEAD … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 98 publications
0
7
0
Order By: Relevance
“…We found that knockout of ARID1A reduced YAP/BRG1 binding, whereas reduced BRG1 expression had no significant effect on ARID1A/YAP binding (Figure 6E), suggesting that ARID1A plays an important role in the formation of the YAP/BRG1 complex. YAP, which is present in the nucleus, can bind to TEAD to form a complex that activates the expression of its downstream genes, thereby promoting tumour development [13,14]. When the expression of ARID1A is inhibited, YAP dissociated from the compound and bound to TEAD (Figure 6F).…”
Section: Arid1a Competitively Binds Yap To Form Arid1a/yap Complexmentioning
confidence: 99%
“…We found that knockout of ARID1A reduced YAP/BRG1 binding, whereas reduced BRG1 expression had no significant effect on ARID1A/YAP binding (Figure 6E), suggesting that ARID1A plays an important role in the formation of the YAP/BRG1 complex. YAP, which is present in the nucleus, can bind to TEAD to form a complex that activates the expression of its downstream genes, thereby promoting tumour development [13,14]. When the expression of ARID1A is inhibited, YAP dissociated from the compound and bound to TEAD (Figure 6F).…”
Section: Arid1a Competitively Binds Yap To Form Arid1a/yap Complexmentioning
confidence: 99%
“…In LSR-knockdown Sawano cells, dobutamine treatment suppressed the enhancement of cell motility and invasion, associated with an increase in the amount of phosphorylated YAP [ 77 ]. Activation of the transcription factor TEAD by YAP increased the expression of genes associated with cell proliferation and survival [ 81 ]. LSR-knockdown Sawano cells induce expression of the Hippo pathway transcription factor TEAD and inducible gene amphiregulin (AREG) [ 77 ].…”
Section: Lsr-related Molecular Mechanisms Leading To Disruption Of En...mentioning
confidence: 99%
“…2 The key effector proteins of the mammalian Hippo signalling pathway, yes-associated protein (YAP) and transcriptional coactivator with a PDZ-binding motif (TAZ), collectively known as YAP/TAZ, regulate cell fate decisions. 3 Activation of the canonical Hippo pathway leads to the formation of the sterility 20-like protein kinase (MST1/2) and Salvador 1 (SAV1) complex, which subsequently phosphorylates the large tumour suppressor (LATS1/2) and MOB kinase activator 1 (MOB1). The activated LATS1/2-MOB1 complex, in turn, phosphorylates YAP/TAZ, resulting in YAP/TAZ retention and degradation in the cytoplasm, thereby preventing their accumulation in the nucleus and downstream gene expression.…”
Section: Introductionmentioning
confidence: 99%
“…The Hippo signalling pathway is an evolutionarily conserved pathway that plays an integral role in regulating glucose metabolism, 1 cellular proliferation, fate regulation, apoptosis, and control of tissue growth and regeneration 2 . The key effector proteins of the mammalian Hippo signalling pathway, yes‐associated protein (YAP) and transcriptional coactivator with a PDZ‐binding motif (TAZ), collectively known as YAP/TAZ, regulate cell fate decisions 3 . Activation of the canonical Hippo pathway leads to the formation of the sterility 20‐like protein kinase (MST1/2) and Salvador 1 (SAV1) complex, which subsequently phosphorylates the large tumour suppressor (LATS1/2) and MOB kinase activator 1 (MOB1).…”
Section: Introductionmentioning
confidence: 99%